Aplikasi Pengecekan Dokumen Digital Tugas Mahasiswa Berbasis Website - Hermawan, Latius; Ismiati, Maria Bellaniar (Universitas Atma Jaya Yogyakarta, 2020)
Abstract. Website-Based Application for Checking Students’ Digital Assignment. Nowadays, technology is not only about computers as it has advanced to smartphones and other things. In UKMC, technology has certainly helped the job. However, in this university, there is no application for checking the plagiarism of the students’ digital assignments, whereas plagiarism is sometimes done by students when working on assignments from online sources. Students’ assignments can be easily done by doing copy and paste without mentioning its reference because students tend to think practically when working on assignments. Plagiarism is strictly prohibited in education because it is not permitted. Therefore, a plagiarism detection application should be created. It applies a string-matching algorithm in text documents to search the common words between documents. By applying the string-matching method in document that match with other documents, an output that will provide information on how similar the text documents are can be generated. After testing, it is obtained that this application can help lecturers and students to reduce the level of plagiarism.Keywords: Application, Plagiarism, Digital, Assignment Abstrak. Sekarang teknologi tidak hanya tentang computer karena kemajuannya telah merambah pada smartphone, dan hal- hal lainnya. Di UKMC, teknologi yang digunakan sudah sangat membantu pekerjaan. Namun di universitas ini, belum ada aplikasi yang dapat memeriksa plagiarisme dari tugas digital mahasiswa padahal plagiarisme terkadang dilakukan oleh mahasiswa saat mengerjakan tugas dari sumber online. Tugas mahasiswa dapat dengan mudah dibuat dengan cara copy-paste tanpa menyebutkan referensi, karena siswa cenderung berpikir praktis ketika mengerjakan tugas. Plagiarisme sangat dilarang dalam pendidikan karena tidak diizinkan. Oleh karena itu aplikasi pendeteksi plagiarisme perlu dibuat. Aplikasi ini menerapkan algoritma pencocokan string dalam dokumen teks untuk mencari kata-kata umum antar dokumen. Dengan metode pencocokan string pada dokumen yang cocok dengan beberapa dokumen lainnya dapat dihasilkan suatu keluaran yang akan memberikan informasi seberapa dekat antar dokumen teks tersebut. Setelah dilakukan pengujian, didapat hasil bahwa aplikasi ini dapat membantu dosen dan mahasiswa untuk mengurangi tingkat plagiarisme.Kata Kunci: aplikasi, plagiarisme, tugas kuliah.